(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Despite extensive natural wave energy resources, and many years of technological developments, only 20.4 MW of wave energy generation was installed in Europe between 2010 and 2022, with only 400 kW still in operation by the end. There is little performance data from the discontinued commercial devices. In contrast, the Albany M4 project aims to provide public-domain access to all data in order to build confidence in wave technology. The Moored MultiMode Multibody (M4) wave energy converter (WEC) is a multi-float attenuator. The two-channel, kW-scale research device, operating in King George Sound, Western Australia, is 24m long, with a 1:2:1 float configuration. This paper evaluates the electro-mechanical power take-off (PTO), based on results of dry tests and at-sea deployment. The wave excitation leads to reciprocating high torque, low speed angular motion at the hinge. A 1:711, multi-stage, planetary gearbox converts the movement to high speed, low torque, driving an off-the-shelf, permanent magnet generator, operating in torque control. Linear damping control has been used for the WEC, with generator reference torque set as proportional to measured speed. An AC:DC active rectifier provides the generator control, with a bidirectional DC:DC converter interface to a super-capacitor energy storage device for power smoothing and voltage regulation. The resulting power is delivered to a load resistor. A rack-mounted power electronic development system was specified, with centralised control, which uses code generation from Simulink. Specifications and system diagrams will be given. This electro-mechanical system was supplied with the two generator/gearbox components coupled back/back, with one emulating the WEC hinge movement and the other as the generator, for dry testing. Factory acceptance tests identified noise and timing problems with the resolvers, which were replaced with incremental encoders. Details of factory acceptance tests will be provided. Dry testing focussed on WEC specific controls - field weakening, linear damping and platform emulation for the electrical machines, and average power extraction for the load – as well as calibrating sensors, checking protection, and defining start-up and shutdown sequences. A key challenge was the need for additional control to address gearbox backlash. Selected dry test results will be presented and discussed, together with the rationale for protection and sequencing. Before deployment, the electrical system was disassembled and transferred to marinised cabinets, so further testing was required to verify correct reconnection and commission the datalogging and network connection, using a crane to move the stern arm of the WEC to create oscillatory motion. At sea, commissioning of the PTO started with pre-charging of the super-capacitors through the generators, in a low sea state, and operation at reduced voltage and power, which demonstrated correct functionality. Despite the need to upgrade the mechanical encoder mounting from the dry-test configuration, the electrical system protection and gearboxes de-loading worked as intended. Selected voltage, current, power and speed waveforms, will be presented. References will be provided.